Effect of ionic liquid segments of copolymer on compatibilization process and dielectric behavior of polylactide/polyvinylidene fluoride blends. Issue 3 (19th August 2020) - Wang, Ping; Cui, Zhaopei; Hu, Xianhai; Xu, Pei; Ding, Yunsheng
Abstract: Biodegradable polylactide (PLA) and polyvinylidene fluoride (PVDF) blends containing the copolymer of PEGMA and 1‐vinyl‐3‐ethylimidazolium bromide (PMI) were prepared, and the effects of ionic liquid segments of PMI on the compatibility of PLA and PVDF were investigated by dielectric relaxation spectroscopy (DRS). PMI can obviously improve the compatibility of PLA and PVDF, compared with the copolymer of PEGMA and vinyl imidazole (PMV). DRS showed that the compatibility of PLA and PVDF was related to the relaxation behavior of the blends, which was identified with Maxwell‐Wagner‐Sillars (MWS) interfacial polarization. The ε ' of PLA/PVDF/PMI blends was much higher than that of PLA/PVDF/PMV blends in the same temperature, resulting from the stimulation of MWS interfacial polarization by the ion mobility of PMI. Abstract : PMI copolymer can improve the compatibility of PLA and PVDF. The ε ' of PLA/PVDF/PMI blends is much higher than that of PLA/PVDF/PMV blends. The compatibility of PLA and PVDF by PMI increases MWS polarization by the ion mobility of PMI.